The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1557/jmr.1993.3131
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical characterization of Sb : SnO2

Abstract: Films of Sb : SnO2 have been formed by vacuum e-beam evaporation. The structural, electrical, and optical properties of these films have been investigated with respect to annealing time and temperature. After heat treatment in an oxygen atmosphere, thin films with a peak transmittance of 98% and 4–9 × 10−3 Ωcm resistivity have been obtained. The barrier heights and energy band diagrams of Sb : SnO2/Si n-n and p-n heterojunctions have been determined by C-V measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(96 citation statements)
references
References 9 publications
1
88
0
1
Order By: Relevance
“…Henceforth, we will refer to those levels as bulk shallow levels. According to electro-physical study data, ionized oxygen vacancies in tin dioxide form shallow donor levels with an energy of ~0.03 and ~0.15eV below the bottom of the CBM [9,10,11]. In electron spin resonance measurements, other authors have observed the existence of donor levels from ~0.15eV up to ~0.30eV underneath the CBM [12].…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Henceforth, we will refer to those levels as bulk shallow levels. According to electro-physical study data, ionized oxygen vacancies in tin dioxide form shallow donor levels with an energy of ~0.03 and ~0.15eV below the bottom of the CBM [9,10,11]. In electron spin resonance measurements, other authors have observed the existence of donor levels from ~0.15eV up to ~0.30eV underneath the CBM [12].…”
Section: -Results and Discussionmentioning
confidence: 99%
“…2,3 In addition, it has potential applications in detecting polluted or toxic gases and other species, [4][5][6] as well as successful use in optoelectronic devices. [7][8][9][10][11][12][13] Oxygen gas monitoring is an important issue in various fields, such as the environment, transportation, medicine, and agriculture. 14,15 Metal oxide semiconductor gas sensors offer an inexpensive and simple method for monitoring gases, due to low cost, small size, and real-time detection.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tin oxide (SnO 2 ) is an n-type semiconductor with a wide band gap (E g = 3.6 eV at 300 K). It is well known for its potential applications in gas sensors [7], transparent conducting electrodes [8], transistors [9], and solar cells [10].…”
Section: Introductionmentioning
confidence: 99%